Disabled learning students before, during, and after the rehabilitation tools: a case study - Ghazali, P.L; Foziah, H.; Tambi, A.M.A.; Mamat, M.; Sukono, .; Bon, A.T. (2019)
Learning disability involves students with reading, writing, and counting disabilities. A clinical work was done amongst six pupils at a primary school in Malaysia. Three of them were learning-disabled pupils and the other three were learning-able pupils. The purpose of the clinical work was to determine whether private lessons, parenting advice, and food supplements as treatments could make significant difference to the assessment results of learning-disabled pupils at school. The basis of test scores in Malay language and Mathematics subjects, the clinical work had shown that learning disabled-students demonstrated significant improvement before, during, and after administering the treatments. Hence, private lessons, parental advice, and food supplements can be used as rehabilitation tools to help learning-disabled pupils learn effectively not unlike their learning-able peers.